2016
DOI: 10.1177/1545968316680491
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Gait Recovery and Limiting Neuropathic Pain After Spinal Cord Injury

Abstract: Most persons living with a spinal cord injury experience neuropathic pain in the months following their lesion, at the moment where they receive intensive gait rehabilitation. Based on studies using animal models, it has been proposed that central sensitization in nociceptive pathways (maladaptive plasticity) and plasticity related to motor learning (adaptive plasticity) share common neural mechanisms and compete with each other. This article aims to address the discrepancy between the growing body of basic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…Studies assessing maladaptive sensory changes after SCI in NHP suggest sensory changes resembling certain human features of central pain including: supraspinal hyper-responsiveness to at-level stimulation, evidence of below-level dysesthesia (depilitation, overgrooming), symptoms that wax and wane over time, and unresponsiveness to opioids[26,99]. However, future studies need to further investigate how the observed sensory changes reflect neuropathic pain phenotypes observed in humans after SCI [100]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing maladaptive sensory changes after SCI in NHP suggest sensory changes resembling certain human features of central pain including: supraspinal hyper-responsiveness to at-level stimulation, evidence of below-level dysesthesia (depilitation, overgrooming), symptoms that wax and wane over time, and unresponsiveness to opioids[26,99]. However, future studies need to further investigate how the observed sensory changes reflect neuropathic pain phenotypes observed in humans after SCI [100]. …”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord plasticity also has been implicated in central pain syndromes, in particular after SCI (Baumbauer, Young, & Joynes, 2009a;Ferguson et al, 2012aFerguson et al, , 2012bMercier, Roosink, Bouffard, & Bouyer, 2017). Based upon animal models, the same mechanisms that lead to spinal plasticity following locomotor training occur due to the nociceptive (pain pathway) input that occurs during a traumatic spinal injury.…”
Section: New Rehabilitation Interventions: the Spinal Cord Is Plasticmentioning
confidence: 99%
“…It is interesting that it appears there is an interaction between developing spinal cord locomotor pattern generators and maladaptive nociceptive processing, given that locomotor training reduces the sensitization to nociceptive stimuli (Ferguson et al, 2012;Mercier et al, 2017). However, the timing of training may be important because wellestablished, untreated, uncontrolled nociceptive input may also reduce the capacity to build central pattern generating circuitry through locomotor training (Ferguson et al, 2012).…”
Section: New Rehabilitation Interventions: the Spinal Cord Is Plasticmentioning
confidence: 99%
“…In patients, tonic pain that may be aggravated by activity (but that does not occur in relation to specific movements) is observed mainly in patients with neuropathic pain, while phasic pain that is specifically associated with a given movement is more typically observed nociceptive musculoskeletal pain. While the effect of phasic musculoskeletal pain on movement is more intuitive and has been studied more extensively using experimental models such as hypertonic saline injection [1,4], neuropathic pain that is unrelated to movement has been shown to be associated with motor alterations in clinical populations or clinical models (e.g., phantom limb pain or neuropathic pain in individuals with a spinal cord injury or a stroke) [2,5]. Studying motor adaptation to this type of pain, using different experimental pain models such as capsaicin, is therefore also warranted.…”
Section: Introductionmentioning
confidence: 99%